Proteasomes: Isolation and Activity Assays. Issue 4 (7th April 2023) - Li, Yanjie; Tomko, Robert J.; Hochstrasser, Mark
Abstract: In eukaryotes, damaged or unneeded proteins are typically degraded by the ubiquitin‐proteasome system. In this system, the protein substrate is often first covalently modified with a chain of ubiquitin polypeptides. This chain serves as a signal for delivery to the 26S proteasome, a 2.5‐MDa, ATP‐dependent multisubunit protease complex. The proteasome consists of a barrel‐shaped 20S core particle (CP) that is capped on one or both of its ends by a 19S regulatory particle (RP). The RP is responsible for recognizing the substrate, unfolding it, and translocating it into the CP for destruction. Here we describe simple, one‐step purification schemes for isolating the 26S proteasome and its 19S RP and 20S CP subcomplexes from the yeast Saccharomyces cerevisiae . A gel filtration step can be added to further enhance purity. We also describe assays for measuring ubiquitin‐dependent and ubiquitin‐independent proteolytic activity in vitro. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Purification of active 26S proteasomes Support Protocol 1 : Growth of yeast strains and production of yeast cell powder Support Protocol 2 : Regeneration of anti‐flag M2 affinity gel Basic Protocol 2 : Purification of the 19S regulatory particle (RP) Basic Protocol 3 : Purification of active 20S CP Basic Protocol 4 : In‐gel peptidase activity assay for 20S CP and 26S proteasomes Basic Protocol 5 : In‐solution peptidase activity assay for 20S and 26S proteasomes Basic Protocol 6 : Measuring degradation of polyubiquitinated SIC1 PY Basic Protocol 7 : Gel filtration of purified proteasomes and subcomplexes